Analysis of Android-Based Applications in Physical Education and Sports: Systematic Review - Muchamad Arif Al Ardha; Nurhasan Nurhasan; Lutfi Nur; Ahmad Chaeroni; Sauqi Sawa Bikalawan; Chung Bing Yang (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Android-based applications have always experienced rapid progress and development over time. This development has an impact on various fields or scopes that exist around it. This study aims to comprehensively review the implementation of android applications in physical education and sports. This study used a systematic review method by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A total of 331 articles from the SCOPUS database were screened to determine 10 relevant articles. These articles were then subjected to a systematic review. The results of the systematic review presented the research that has been conducted covering several fields, such as learning media, training, health, and sport biomechanics. The presentation of research data from the review results contributed to the development of research in the field of Android-based applications in physical education and sports. On the other hand, research related to Android-based applications needs to be done intensely in physical education.